2000
DOI: 10.1002/(sici)1097-4652(200006)183:3<399::aid-jcp13>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Myc/Max/Mad network members in adipogenesis: Inhibition of the proliferative burst and differentiation by ectopically expressed Mad1

Abstract: Transcription factors of the Myc/Max/Mad network affect multiple aspects of cellular behavior, including proliferation, differentiation, and apoptosis. Recent studies have shown that Mad proteins can inhibit cellular growth and transformation and thus antagonize the function of Myc proteins. To define further the contribution of these proteins to cellular growth control, we have studied the expression of the respective genes and proteins in 3T3-L1 cells, both upon serum stimulation of quiescent cells and durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
24
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 54 publications
9
24
0
Order By: Relevance
“…Moreover, Mnt ± Max heterodimers appear to be amongst the most abundant Maxcontaining complexes (Sommer et al, 1998;Pulverer et al, 2000). Therefore, we have begun to characterize the regulation of mnt gene expression.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Moreover, Mnt ± Max heterodimers appear to be amongst the most abundant Maxcontaining complexes (Sommer et al, 1998;Pulverer et al, 2000). Therefore, we have begun to characterize the regulation of mnt gene expression.…”
supporting
confidence: 55%
“…Such an element may allow the e cient translation of mnt transcripts under conditions when the activity of the cap binding complex eIF4F is reduced, as has been observed for the VEGF IRES during hypoxia and the XIAP and c-myc IRESs during apoptosis (Stein et al, 1998;Holcik et al, 1999;Stoneley et al, 2000). In this regard, it is noteworthy that Mnt is synthesized in quiescent ®broblasts and in terminally di erentiated adipocytes (Pulverer et al, 2000). Given the ability of Mnt to suppress Mycmediated cellular transformation, the function and mechanism of the mnt IRES warrant further investigation.…”
Section: Oncogenementioning
confidence: 55%
“…In many in vitro systems, the regulation of the c-myc/max/ mad network has been shown to rely on the opposing expression patterns of c-myc and mad family members, whereas max expression is constitutive (22,25). We (29) have reported previously that c-Myc protein content is not changed even though c-myc RNA expression is decreased as proliferating hepatocytes growth arrest during liver development, but c-Myc localization switches from a diffuse nuclear to a nucleolar pattern (29).…”
Section: Discussionmentioning
confidence: 99%
“…We also examined the expression of mad4 and mad3 in the fetal and adult liver. In agreement with previous studies in other systems, we found mad4 to be induced in the quiescent adult, whereas mad3 was elevated in the fetus (12,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation